Investigation of miRNA and mRNA Co-expression Network in Ependymoma - Liu, Feili; Dong, Hang; Mei, Zi; Huang, Tao (Frontiers in Bioengineering and Biotechnology, 2020)
Ependymoma (EPN) is rare primary tumor of central nervous system that affects both children and adults. Despite definition and classification of distinct molecular subgroups, there remains a group of EPNs with a balanced genome, which makes it difficult to predict prognosis of patients with EPN. The role of miRNA-mRNA network on EPN is still poorly understood. We assessed involvement of miRNA-mRNA pairs in EPN by applying weighted co-expression network analysis (WGCNA) approach. Using whole genome expression profile analysis followed by functional enrichment, we detected hub genes involved in active proliferation and DNA replication of nerve cells. Key genes including CYP11B1, KRT33B, RUNX1T1, SIK1, MAP3K4, MLANA and SFRP5 identified in co-expression network were regulated by miR-15a and miR-24-1. This seven miRNA-mRNA pairs were considered to influence not only pathways in cancer and tumor suppression process, but also MAPK, NF-kappaB and WNT signaling pathways which were associated with tumorigenesis and development. This study provides novel insight into potential diagnostic biomarkers of EPN and may have a value in choosing therapeutic targets with clinical utility.